Employers' requirements for brand managers: A comparative study in the US and Ukraine - Zuzana Wroblowská (Trends Economics and Management, 2019)
Purpose of the article: The author's interest focuses on brand managers as brands are among the factors strongly contributing to increasing intellectual capital of any organization. This paper provides a comparison of requirements for brand managers at the phase they are addressed by employers in both the US and Ukraine. The author finds it useful to focus on requirements for skills, knowledge and work experience, as the findings have potential to inspire applicants for vacancies in the product management departments and tertiary education providers. Methodology/methods: Using a re-applied Berelson's method of content analysis makes it possible to analyse and discuss the requirements for job of brand managers in different countries. The hypothesis regarding the analysed variable's independence on the sign representing the country where the job advertisements were posted was tested applying chi-square statistics. Scientific aim: The objective was to verify that the requirements for brand manager positions in Ukraine and the US do not differ. The hypothesis was formulated as follows: American and Ukrainian employers do not raise different recruitment requirements in terms of required practice and education, knowledge, technical and strategic competence for brand manager posts. Findings: The comparison of the frequency of requirements for the applicants in Ukraine and the US showed differences. When testing the set of requirements for work experience and required practice for brand manager positions in Ukraine and the US, the Pearson's test confirmed the differences for & = 0.05, & = 0.01, and & = 0.001. The Person's test also confirmed the difference in the group classified under the letter "Q" concerning education, specific knowledge, business management skills and transferable skills at all tested levels. Conclusions: The findings raise more questions, both about the knowledge and skills of brand managers, and the nature of their role in the brand management process.
Keywords: D83; M12; M31; M51; 650; brand manager; intellectual capital; knowledge; product management; skills; strategic competence